Letter from Janke & Kunkel A.-G. to Georg Bredig - Janke & Kunkel AG (1924)
Letter from Janke & Kunkel A.G., a laboratory equipment manufacturer and trading company of pharmaceutical supplies. Founded in Cologne, Germany in 1910 by Curt Janke and Max Kunkel, the company faced destruction and upheaval during World War II. In 1948, the company revived itself as IKA-Works, Inc. which continues to produce laboratory equipment, and analytical and process technology today.
Keywords: Chemical laboratories--Equipment and supplies; Scientific apparatus and instruments industry; Scientific apparatus and instruments; Bredig, Georg, 1868-1944